2020
DOI: 10.1136/tsaco-2020-000581
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience with the Quantra QStat System in adult trauma patients

Abstract: BackgroundWhole blood viscoelastic testing (VET) devices are routinely used in a variety of clinical settings to assess hemostasis. The Quantra QStat System is a cartridge-based point of care VET device that measures changes in clot stiffness during coagulation and fibrinolysis using ultrasound detection of resonance. The objective of this study was to assess the ability of the Quantra QStat System to detect coagulopathies in trauma patients.MethodsA multicenter observational study was conducted on adult subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…Reagents consist of a consumable, ready-to-use cartridge with four parallel channels prefilled with specific lyophilized reagents [22]. There are currently two kinds of cartridges: the QPlus cartridge and the QStat one dedicated to exploring fibrinolysis [23]. Measurements of clot coagulation time with (CTH) or without (CT) heparinase and coagulation initiation with kaolin, clot stiffness (CS) after initiation with thromboplastin, and fibrinogen contribution to the overall clot stiffness (FCS) after platelet inhibition with abciximab are performed simultaneously in four parallel channels.…”
Section: Quantramentioning
confidence: 99%
See 1 more Smart Citation
“…Reagents consist of a consumable, ready-to-use cartridge with four parallel channels prefilled with specific lyophilized reagents [22]. There are currently two kinds of cartridges: the QPlus cartridge and the QStat one dedicated to exploring fibrinolysis [23]. Measurements of clot coagulation time with (CTH) or without (CT) heparinase and coagulation initiation with kaolin, clot stiffness (CS) after initiation with thromboplastin, and fibrinogen contribution to the overall clot stiffness (FCS) after platelet inhibition with abciximab are performed simultaneously in four parallel channels.…”
Section: Quantramentioning
confidence: 99%
“…Two used the ClotPro device [24,68] and its ready-to-use tPA-test reagents, which are now CE-marked, whereas the two others [39,40] used an in-house ROTEM assay with two different tPA concentrations (named TEM-tPA), making a comparison between them problematic. No study has investigated a defective fibrinolysis using the Quantra device into the COVID-19 context, whereas a new dedicated reagent cartridge is now available [23]. The four articles share the same conclusion that increased clot maximum amplitude and decreased lysis index reflect an increase in clot strength and a decreased fibrinolytic capacity, results that need to be confirmed with a larger cohort.…”
Section: Ability Of Vets To Detect Hypofibrinolysis State and Associamentioning
confidence: 99%
“…This study identifies potential cut‐off values for QPlus FCS and PCS proposed for use in place of or in conjunction with laboratory‐based assays fibrinogen and platelet thresholds to guide transfusion decisions in surgical patients. Several groups have assessed the utility of the devices when compared to other VHA and standard laboratory tests in adult patients undergoing cardiac surgery 28–30 and in traumatized patients 31 . All these studies found the Quantra QPlus useful in predicting the need for hemostatic products.…”
Section: Technology and Clinical Applicationsmentioning
confidence: 99%
“…The Quantra system does not provide a TF activated clotting time (CT) and is limited to assess the intrinsic pathway (activation by kaolin). Furthermore, hyperfibrinolysis can only be detected in the Quantra system using a specific cartridge (QStat cartridge) [33]. No data are available whether the Quantra system can detect fibrinolysis shutdown which is an important issue in bacterial sepsis and COVID-19 [34][35][36][37].…”
Section: The Viscoelastic Tests: Parameters and Interpretationmentioning
confidence: 99%